EFFECT OF ACUPRESSURE THERAPY POINT LI 4, SP 6, AND BL 60 ON DURATION OF THE FIRST STAGE OF LABOR IN PRIMIGRAVIDA AND NEWBORN’S APGAR SCORE - Fara Imelda Theresia Patty; Suhartono Suhartono; Ngadiyono Ngadiyono; Mardiyono Mardiyono (Belitung Raya Foundation, Indonesia, 2017)
Background: The prolonged partus is one of the causes of maternal deaths marked by the slow progress of labor. Induction of labor and caesarean section is a common procedure performed on long-term partus events to end pregnancy. The birth acupressure technique is a complementary method to activate the hormone oxytocin at a certain point to use to soften the cervix and increase contraction. Objective: To examine the effect of acupressure point LI4, SP6 and BL60 on the duration of the first stage of labor and APGAR score of newborns in primigravida. Methods: This research employed a quasi-experimental study with posttest control group design. It was conducted at the Public Health Center of Trauma and Public Health Center of Palaran Samarinda, East Kalimantan, Indonesia. There were 40 respondents selected using purposive sampling, which 20 respondents assigned in the experiment and control group. The duration of the first stage of labor was assessed using partograph and APGAR score was assessed using APGAR score assessment sheets. Mann Whitney test was used for data analysis Results: Findings showed that the duration of the first stage of labor in the experiment group was 187 minutes and in the control group was 307 minutes. Mann Whitney test obtained p-value 0.001 (<0.05), which indicated that there was a statistically significant difference of the duration of the first stage of labor between both groups. However, Mann Whitney test for APGAR score showed p-value 0.114 (>0.05), which indicated that there was no significant difference of APGAR score in the experiment and control group. Conclusion: There was a significant effect of acupressure on the duration of the first stage of labor, but no effect of the APGAR score. Therefore, acupressure may be recommended to shorten the duration of the first stage of delivery in primigravida.